Design and Application of Special Sensors and Internet of Things (IoT)-based Wireless System for Agricultural Information Monitor. (September 2020) - Li, Ganqiong; Li, Denghua; Chen, Wei; Zhang, Yongen; Xu, Shiwei
Abstract: Efficient and accurate monitoring of agricultural information is the basis of implementing precision agriculture and improving agricultural productivity. In order to monitor agricultural production information comprehensively, accurately and in real time, an agricultural information monitoring system based on Internet of things (IoT) was developed, which could realize online collection and intelligent management of agricultural information. The system is composed of three layers: perception layer, network layer and application layer. The perception layer consists of various agricultural special sensors, radio-frequency identification (RFID) tag module, ultrahigh frequency RFID read/write device and other measurement modules. The network layer is composed of several ZigBee wireless communication nodes, gateway modules, coordinator modules and remote servers. The application layer includes information application system and user terminal. Sensors were developed and connected by wireless networking technology, and the sensor data was gathered and transmitted to the server terminal in real-time. Mobile terminal system was developed synchronously. The system could be applied to various agricultural scenes, such as field crops, animal husbandry, and has the characteristics of high scalability, intelligence, easy to management and use.